2020
DOI: 10.1128/msystems.00648-20
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Contractile Injection System Gene Cluster Found in a Majority of Healthy Adult Human Microbiomes

Abstract: Many commensal bacteria antagonize each other or their host by producing syringe-like secretion systems called contractile injection systems (CIS). Members of the Bacteroidales family have been shown to produce only one type of CIS—a contact-dependent type 6 secretion system that mediates bacterium-bacterium interactions. Here, we show that a second distinct cluster of genes from Bacteroidales bacteria from the human microbiome may encode yet-uncharacterized injection systems that we term Bacteroidales injecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…1b ) and Parabacteroidetes genera. Bacteroides was recently reported by the Shikuma group as being eCIS-rich 30 .
Fig.
…”
Section: Resultsmentioning
confidence: 96%
“…1b ) and Parabacteroidetes genera. Bacteroides was recently reported by the Shikuma group as being eCIS-rich 30 .
Fig.
…”
Section: Resultsmentioning
confidence: 96%
“…The copyright holder for this preprint this version posted October 25, 2022. ; https://doi.org/10.1101/2022.10.24.513551 doi: bioRxiv preprint machinery Hydroides uses to sense these products could lead to broader discoveries about mechanisms and tools for host-microbe interactions. For example, we found that gene clusters encoding Contractile Injection Systems originally discovered to promote Hydroides metamorphosis are strikingly similar to gene clusters found in Bacteroidales bacteria from healthy human microbiomes 62 . Moreover, understanding the payload delivery and targeting mechanism of the MACs produced by P. luteoviolacea could enable us to produce new types of therapeutic delivery systems 63 .…”
Section: Biotechnology and Bacterial Productsmentioning
confidence: 61%
“…The products bacteria produce to promote Hydroides metamorphosis and the machinery Hydroides uses to sense these products could lead to broader discoveries about mechanisms and tools for host‐microbe interactions, and how these interactions evolve on a genetic and chemical level. For example, we found that gene clusters encoding Contractile Injection Systems originally discovered to promote Hydroides metamorphosis are strikingly similar to gene clusters found in Bacteroidales bacteria from healthy human microbiomes 59 . Moreover, understanding the payload delivery and targeting mechanism of the MACs produced by P. luteoviolacea could enable new types of therapeutic delivery systems 60 …”
Section: Resultsmentioning
confidence: 79%
“…For example, we found that gene clusters encoding Contractile Injection Systems originally discovered to promote Hydroides metamorphosis are strikingly similar to gene clusters found in Bacteroidales bacteria from healthy human microbiomes. 59 Moreover, understanding the payload delivery and targeting mechanism of the MACs produced by P. luteoviolacea could enable new types of therapeutic delivery systems. 60…”
Section: The Future Of Hydroidesmentioning
confidence: 99%